Acculturation and Responsiveness to Social Responsibilities of Aeta Community - April Christian D De Leon (ASEAN Multidisciplinary Research Journal, 2021)
Aeta culture has evolved into complex form brought by its exposure to different pressures from the mainstream community. Yet, there is an undeniable dearth when it comes to studies concerning its current status. The purpose of this study is to determine the acculturation strategies and the responsiveness to social responsibilities of the Aeta community. In relation, Berry’s Model of Acculturation was used to identify the strategies that the community use, while the Triple Bottom Line Model was used to indicate social responsibilities. To facilitate 16,664 respondents, the researcher used random sampling technique. The foundation of its confidence level was set using Slovin’s formula. The researcher used a purposive checklist with an interview schedule to obtain data. Utilizing Chi-square test analysis to test the first hypothesis, it was found out that the highest educational attainment of the respondents is statistically related to their level of responsiveness in social responsibilities. Furthermore, the result posits that responsiveness to social responsibilities along environmental, altruistic, and economic responsibilities of the Aeta was found to be significantly different to their extent of practice in integration strategy. The result suggests that strengthening the engagement of Aetas on the mainstream community while providing them practical and contextualized education about the pros and cons of their own and non-Aeta cultures and giving them freedom to decide what to take, change and retain on it, will deliver them sense of self-determination, integrity and a responsive culture anchored on social responsibilities.